Kebijakan Hedging dengan Derivatif Valuta Asing pada Perusahaan Go Public di Indonesia Periode 2009-2012 - Kartini Kartini; Rif'ad Adista Hasridha (Jurnal Aplikasi Bisnis, 2017)
This study aims to test the Hedging Policy with Foreign Currency Derivatives Companies Go Public In the period 2009-2012 in Indonesia have hedging dependent variable, and independent variables consist of DER, ICR, MBV, LnTA and CR. The method in this study using a tool such as Regression Logit (Binary Logit) were further tested by assessing the feasibility of the regression model (Goodness of fit test) and a value R2 Karke Nagel. Testing the hypothesis in this research using multiple ways of testing, ie Simultaneous testing using Omnibus Test of Model Coefficients. Partial and testing employ the Wald statistical test method of logistic regression results. The result of the logit regression is used to determine how far influence the policy of hedging the company went public in Indonesia. The results of this study indicate that the independent variables consist of DER, ICR, MBV, LnTA and CR simultaneously affect hedging policy at the company went public in Indonesia. Partially ICR affect the hedging policy of the company went public in Indonesia, while DER, MBV, LnTA and CR had no effect on the hedging policy of the company went public in Indonesia.